An exploration of teaching and learning in an isiXhosa communicative language skills course in a medical school - Tyam, Nolubabalo (School of Languages and Literatures, 2016)
This thesis reports on research conducted into the teaching and learning of an isiXhosa Communication Skills course as a Second Language (SL) at the University of Cape Town (UCT). The research was an exploration of an isiXhosa language teaching pedagogy with a particular focus on learning and teaching and the usage of isiXhosa in the isiXhosa Communications Skills classroom. In doing this research, I wanted to know what could be the cause of these attitudes. Questions that need to be considered in developing this pedagogy are: What are the benefits of its usage in the classroom? What are the language pedagogies that the teachers are struggling with? The study was carried out with second year medical students. In this study, questionnaires were distributed to 63 research subjects. Four classroom observations were carried out and 12 students were interviewed. I observed that teachers as a group had characteristic pedagogical styles and approaches. The teachers were using more teacher-centred method, relying heavily on the use of textbooks, focused more on the teaching of pure isiXhosa language and used less varied techniques of instruction and engagement. There was little evidence of learner-centred teaching and incorporation of more communicative, interactive lessons and activities that help students for speaking competence. Students had strong positive attitudes towards learning isiXhosa communication skills. The students' views from the interviews and classroom observations point towards broadly issues of learning second language and pedagogy in learning and teaching. Students seemed to be concerned and frustrated with the fact that they cannot speak in isiXhosa with the patients. They felt that learning isiXhosa was essential for their future careers, and the ability to speak isiXhosa would be beneficial for their work. The students' interviews reinforced the conclusions that I drew from the classroom observations and yielded insights into how teachers teach a Second Language.